Chromobacterium violaceum Related Urinary Tract Infection: A Case Report - Imola Jamir; Lakshmi Shanmugam; Gopinath Karuppiah; Stalin Viswanathan; Jharna Mandal (Journal of Clinical and Diagnostic Research, 2023)
Chromobacterium violaceum (C. violaceum) is a motile, gram-negative bacilli found in water and moist soil. Infections due to C. violaceum are uncommon but have a significant mortality rate (upto 80%) due to their tendency for haematogenous dissemination resulting in sepsis. The organism has been reported to cause skin and soft tissue infections, diarrhoea, bacteremia, and visceral abscess; Urinary Tract Infection (UTI) is rarely seen. Here, a 41-year-old male diabetic who presented with fever, altered sensorium and burning micturition caused by C.violaceum is presented. Initial investigations revealed an increased Random Blood Sugar (RBS) level, high anion gap metabolic acidosis with normal renal and liver function (except for hypoalbuminemia). Diabetic ketoacidosis, probable meningitis and urosepsis were considered as differential diagnosis. On culture of urine sample, C. violaceum was isolated which was susceptible to all the antibiotics tested except amikacin. Blood culture was reported as sterile. Patient was successfully treated with susceptible antibiotic (ciprofloxacin) and repeat culture of urine was also sterile. Early diagnosis and adequate treatment is necessary to reduce the risk of progression to fatal infection.